Neonatal systemic juvenile Xanthogranuloma with Hydrops diagnosed by Purpura skin biopsy: a case report and literature review - Yohji Uehara; Yuka Sano Wada; Yuka Iwasaki; Kota Yoneda; Yasuhisa Ikuta; Shoichiro Amari; Hidehiko Maruyama; Keiko Tsukamoto; Tetsuya Isayama; Kenichi Sakamoto; Yoko Shioda; Osamu Miyazaki; et al. (BMC, 2021)
Abstract Background Systemic juvenile xanthogranuloma is a very rare disease typically presents as skin lesions with yellow papules or nodules and is sometimes fatal. We report a case of congenital neonatal systemic juvenile xanthogranuloma with atypical skin appearance that made the diagnosis difficult. Case presentation A preterm Japanese female neonate with prenatally diagnosed fetal hydrops in-utero was born with purpuric lesions involving the trunk and face. Since birth, she had hypoxemic respiratory failure, splenomegaly, anemia, thrombocytopenia, coagulopathy, and was transfusion dependent for red blood cells, fresh frozen plasma, and platelets. Multiple cystic lesions in her liver, part of them with vascular, were detected by ultrasound. A liver biopsy was inconclusive. A skin lesion on her face similar to purpura gradually changed to a firm and solid enlarged non-yellow nodule. Technically, the typical finding on skin biopsy would have been histiocytic infiltration (without Touton Giant cells) and immunohistochemistry results which then would be consistent with a diagnosis of systemic juvenile xanthogranuloma, and chemotherapy improved her general condition. Conclusions This case report shows that skin biopsies are necessary to detect neonatal systemic juvenile xanthogranuloma when there are organ symptoms and skin eruption, even if the skin lesion does not have a typical appearance of yellow papules or nodules.